(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Endoparasitic infection and histopathological effects in the laboratory rat, Long-Evans (Rattus norvegicus Berkenhout 1769) was evaluated. Five species of helminth parasites from two taxonomic groups were identified. They were -Cestodes (Vampirolepis nana Siebold, 1852 and Hymenolepis diminuta Rudolphi, 1819) and Nematodes (Citellina dispar Prendel, 1928; Heterakis spumosa Schneider, 1866 and Syphacia muris Yamaguti, 1941). All the worms were collected from the alimentary tract of the Long-Evans. The prevalence of infection was found highest in caecum (95.83%) and the intensity of infestation was found highest in anterior parts of the intestine (51.33±10.63). The histopathological study of helminth infected alimentary canal showed that the intestinal wall was severely damaged. Key words: Nematodes, Cestodes, Prevalence, Vampirolepis nana, Hymenolepis diminuta, Citellina dispar, Heterakis spumosa and Syphacia muris. DOI: 10.3329/bjsir.v44i2.3673 Bangladesh J. Sci. Ind. Res. 44(2), 207-210, 2009